2018
DOI: 10.1123/ijsnem.2017-0397
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Indicators of Low Energy Availability in Elite Female Sprinters

Abstract: Low energy availability (LEA), and subsequent relative energy deficiency in sport, has been observed in endurance, aesthetic, and team sport athletes, with limited data on prevalence in athletes in short-burst activities such as sprinting. We examined prevalence of signs and symptoms of LEA in elite female sprinters at the start of the training season (PRE), and at the end of a 5-month indoor training period (POST). Four of 13 female sprinters (31%) presented at PRE testing with at least one primary (amenorrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 33 publications
2
27
0
1
Order By: Relevance
“…Preparation phases of training introduce more event-specific technical work, with increased strength and conditioning volume (Schiffer, 2011(Schiffer, , 2012. When the training load is at its highest, CE athletes can be at risk of energy imbalances, injuries, overtraining, and other LEA symptoms, similar to those previously reported in sprinters (Sygo et al, 2018). Thus, quickly absorbed and easily digested CHO and PRO snacks are needed for these training days, and can include both commercially made products and whole foods, such as sport drinks, PRO shakes, sport bars, gels, pureed fruit pouches, trail mixes, peanut butter sandwiches, fruit and yogurt smoothies, and meat and cheese sandwiches.…”
Section: Nutrition Strategies To Support Training Adaptations For Ce supporting
confidence: 77%
See 1 more Smart Citation
“…Preparation phases of training introduce more event-specific technical work, with increased strength and conditioning volume (Schiffer, 2011(Schiffer, , 2012. When the training load is at its highest, CE athletes can be at risk of energy imbalances, injuries, overtraining, and other LEA symptoms, similar to those previously reported in sprinters (Sygo et al, 2018). Thus, quickly absorbed and easily digested CHO and PRO snacks are needed for these training days, and can include both commercially made products and whole foods, such as sport drinks, PRO shakes, sport bars, gels, pureed fruit pouches, trail mixes, peanut butter sandwiches, fruit and yogurt smoothies, and meat and cheese sandwiches.…”
Section: Nutrition Strategies To Support Training Adaptations For Ce supporting
confidence: 77%
“…Attaining an optimal body composition can be more challenging for CE athletes than for athletes in other events, and it is often personal to each athlete, depending on individual event strengths and weaknesses. Athletes may benefit from a slightly higher fat mass and LM in the early part of the season to support recovery and to limit indicators of LEA that may emerge over the season (Sygo et al, 2018). Muscle mass may increase during phases where strength is the focus, but decrease in phases where running and jumping are prioritized, due to a higher energy expenditure in running workouts and reduced resistance training load (O'Connor et al, 2007).…”
Section: Periodized Body Composition For Jumpers Throwers and Ce Atmentioning
confidence: 99%
“…The risk of low EA has been investigated using surrogate markers or self-reported symptoms of low EA in various athlete populations including elite para-athletes [34], adolescent/young adult [35,36] and Olympic athletes [40], female sprinters [41], male jockeys [39] and recreationally active individuals [33,37], and ranges from 14% to 63% ( Table 3). The largest cross-sectional study investigating self-reported health and performance outcomes linked to low EA and RED-S [5] placed emphasis on including body systems beyond reproductive function and bone health such as metabolic, haematological, psychological and cardiovascular health and gastrointestinal function.…”
Section: Low Energy Availability Riskmentioning
confidence: 99%
“…These results are consistent with an earlier report by Sundgot-Borgen and Torstveit (2004), who reported a 24% prevalence of EDs in female national team endurance athletes compared with 9% among male endurance athletes. In contrast to running events, literature on the prevalence of LEA with and without EDs/DE in sprint and jumping events is less well characterized (Table 2; Sygo et al, 2018). Sundgot-Borgen and Torstveit (2004) reported a prevalence of EDs in 3% and 6% of male and female national team athletes in sprint and throwing events, respectively.…”
Section: Prevalence Of Lea De and Eds In Athleticsmentioning
confidence: 99%